Surrogate molecular subtyping of breast carcinomas– A study on recent modifications and their clinicopathological significance - Dr. Priyanka A; Dr. Muthu Sudalaimuthu; Dr. G. Shivashekar (Tropical Journal of Pathology and Microbiology, 2021)
Context: Breast carcinoma is a heterogenous disease with varied clinicopathological features and response to therapy. Molecular classification through gene studies helps in planning therapy but has economic constraints. Hence immunohistochemical subtyping of breast carcinomas has been used as a surrogate method. Criteria for this subtyping has undergone many modifications since it was originally proposed.Objectives: To immunohistochemically subtype breast carcinomas based on St.Gallen 2017 guidelines and analyse the differences in clinicopathological parameters like age, tumour size, histopathological grade and lymph node staging between the various subtypes.Materials and methods: The study was done retrospectively at a tertiary care health centre in South India on breast carcinoma patients from January 2017 to June 2020. Immunohistochemistry was done with antibodies to the Estrogen receptor, Progesterone receptor, Human epidermal growth factor receptor-2 (HER-2) and Ki-67. Immunohistochemical Subtypes were correlated with Clinicopathological features.Results: The study had 107 cases. Hormone receptor (HR) positive HER-2 negative was the most common subtype (55 cases, 51.4%). This subtype frequently presented without nodal metastasis (58.2%) and in >50 years of age (56.4%). Triple-negative subtype frequently presented with grade III (69.2%), highest nodal metastasis stage (38.5%) and in < 50 years of age (69.2%). Difference in grade, tumour size and nodal metastasis stage between the different subtypes was significant with p <0.001.Conclusion: St.Gallen 2017 guidelines for immunohistochemical subtyping classified breast carcinomas into groups that differed significantly in their clinicopathological features. Further studies on differences in treatment response and survival rate differences between these different subtypes are needed.